Impacts of rural dual economic transformation on the inverted-U curve of rural income inequality: An empirical study of Tianjin and Shandong provinces in the People's Republic of China - Zongshen Chen; Wu Ting; Kang Jian (Asian Development Bank Institute (ADBI), 2017)
Using a case study about rural Tianjin and Shandong provinces, we try to explain what mechanism affects income inequality in rural areas, especially how rural dual structural transformation leads to the income inequality "inverted-U" Curve in some developed areas in the People's Republic of China (PRC). We choose Tianjin to represent developed provinces, which depend on nonagricultural and urban agricultural development modes, and take Shandong Province to represent areas dominated by traditional agriculture. We can clearly observe that the changes in rural income inequality are roughly consistent with the changes in dual economic transformation in different regions. A marginal decomposition analysis on the Gini coefficient changes of income inequality shows that the distribution effect always accounts for the dominant position and determines the inequality change direction, both in Tianjin and Shandong. By comparison, we find that the dual transformation is sure to affect and change the sectoral labor participation rate directly, and then affect and change the within-sector income inequality, and further to make total income inequality go up or down. Through this empirical and comparative study, we suggest some policies to both grow rural income and reduce income inequality in rural PRC, which means accelerating growth in order to go beyond the "inverted-U curve" turning point.
Keywords: O15; D31; 330; Inverted-U curve; income inequality; Gini coefficient; dual economic transformation